Village Chief Authority in Making Inheritance Information for Indonesian Citizens of Chinese Descent - Hanifah Hanifah; Gunawan Djajaputra (Green Publisher Indonesia, 2023)
Inheritance Certificate is a document that proves who is entitled to inherit from the heir, so that there is no doubt or dispute over the inheritance information, it is important to know who is authorized to make the Inheritance Statement. The mechanism of the certificate of inheritance issued by the Lurah based on the Regulation of the Minister of Agrarian Affairs Number 3 of 1997 concerning the Provisions of PP No: 24 of 1997 concerning Land Registration Article 111 paragraph (1) letter c of Making Inheritance Certificate (SKW). This type of research is normative legal research that uses legal and conceptual approaches. This study used primary and secondary legal sources. This is also written and considered to answer questions to clarify the authority of the Lurah in making the inheritance of Indonesian citizens of Chinese descent. The results show that the authority of the Lurah in making SKW for Indonesian citizens of Chinese descent is only regulated in the Implementation of Article 111 paragraph 1 letter c number 4. the legal consequences of the inheritance certificate made by the Lurah against Indonesian citizens of Chinese descent are null and void, and in making SKW in Kelurahan Indonesian citizens of descent, they must refer to Article 111 paragraph 1 letter c number 4 of the Regulation of the Minister of Agrarian Affairs and Spatial Planning.